Analisis Kinerja Keuangan pada Perusahaan PT Kalbe Farma Tbk. Sebelum dan Sesudah Covid-19 - Priyanto, Sigit; Suselo, Dedi (Ikatan Da'i Indonesia, 2023)
This study aims to analyze the comparison of the company's financial performance at PT. Kalbe Tbk. before and after Covid-19. Financial performance is calculated using financial ratios which include quick ratio, return on assets, debt to equity ratio, and total assets turn over. The population and sample in this study are the financial statements of the company PT. Kalbe Farma Tbk for the period 2016-2020 which is listed on the IDX. The data analysis method used is the Independent Sample T-test which was previously tested for normality. The results of data analysis show that from the four ratios tested there are no significant differences, so it can be concluded that there is no difference in financial performance at PT. Kalbe Farma Tbk. before and after Covid-19.